2007
DOI: 10.1007/s00595-006-3436-x
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Schwannoma: Report of a Case

Abstract: We report a case of esophageal schwannoma in a 46-year-old woman who presented with rapidly progressive dyspnea and dysphagia. Chest computed tomography showed a large mediastinal mass, which was extrinsically compressing the trachea, widely adjacent to the upper thoracic esophagus. We performed an axillary right thoracotomy to enucleate the tumor, which was located in the esophageal muscle layer. A definite diagnosis of esophageal schwannoma was made from the pathologic findings, which included positive immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Esophageal schwannomas are exceedingly rare with only a handful of cases reported in the literature [3]. A literature review performed for the past decade, 2005 -2015, revealed a total of 21 cases of which two cases were of concurrent esophageal schwannomas [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The surgical approaches to these include four thoracoscopic, six thoracotomy, five cervical approaches, and five esophagectomies or partial esophagectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal schwannomas are exceedingly rare with only a handful of cases reported in the literature [3]. A literature review performed for the past decade, 2005 -2015, revealed a total of 21 cases of which two cases were of concurrent esophageal schwannomas [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The surgical approaches to these include four thoracoscopic, six thoracotomy, five cervical approaches, and five esophagectomies or partial esophagectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of this tumor include dysphagia, dyspnea [ 1 , 3 ], chest pain, and hematemesis, and appear when the tumor increases in size. Imaging studies (positron emission tomography, computed tomography, and magnetic resonance imaging) are useful for the confirmation of esophageal tumor [ 1 , 4 , 5 ]. Endoscopic ultrasonography-guided fine needle aspiration biopsy is not always useful for diagnosis, as in our cases [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of this disease include dysphagia, dyspnea, and chest pain, and are likely to appear and worsen as the schwannoma increases in size [6]. Fluorodeoxyglucose positron emission tomography as well as CT and MRI are reportedly useful for the confirmation of mediastinal tumors [7].…”
Section: Discussionmentioning
confidence: 99%